Obtenção e caracterização de nanopartículas de quitosana - Tavares, Idylla Silva (2011)
Chitosan nanoparticles have been used in several systems for the controlled release of drugs. The aim of this study was to obtain and characterize chitosan nanoparticles prepared by the method of coacervation / precipitation using sodium sulfate at different concentrations as the crosslinking agent. The characterization was done using zeta potential and small angle Xray scattering, SAXS. The dispersions of chitosan were obtained at pH 1 and pH = 3. The results of zeta potential at pH = 1 ranged from +64.8 to +29.27 mV and for pH = 3 they varied from +72.4 to +23.48 mV, indicating that the chain of chitosan is positively charged in acidic pH and the behavior of nanoparticles in terms of surface charge was independent of pH. However, the results indicated a dependence of particle size in relation to pH. This difference in behavior was explained by the influence of enthalpic and entropic components